2021
DOI: 10.3389/fmed.2021.654524
|View full text |Cite
|
Sign up to set email alerts
|

Dentistry Amidst the COVID-19 Pandemic: Knowledge, Attitude, and Practices Among the Saudi Arabian Dental Students

Abstract: Background: The recent pandemic outbreak has created a huge impact on dentistry. Dental students and dental professionals are at a higher risk because dental practice comprises close communication and widespread exposure to blood, saliva, and other body fluids. It is imperative to evaluate the knowledge and perceptions regarding Coronavirus (COVID-19) among budding dentists.Aim: To assess the knowledge, attitude, and practices of dental students regarding dental practices during COVID-19.Materials and methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
2
25
0
4
Order By: Relevance
“…Our study found a higher score among postgraduate students than undergraduates, because clinical students rely more on science-based resources, such as the Ministry of Health rather than social media [43]. There were significant differences found in the COVID-19 knowledge and protective behaviors among clinical and preclinical students, and the results were consistent other studies that were conducted in Turkey, China, Saudi Arabia, Italy, and Nigeria [18,30,[43][44][45][46]. The lower knowledge scores among undergraduate students highlight the need to refine the current dental curriculum, including infectious diseases epidemiology and control practices.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study found a higher score among postgraduate students than undergraduates, because clinical students rely more on science-based resources, such as the Ministry of Health rather than social media [43]. There were significant differences found in the COVID-19 knowledge and protective behaviors among clinical and preclinical students, and the results were consistent other studies that were conducted in Turkey, China, Saudi Arabia, Italy, and Nigeria [18,30,[43][44][45][46]. The lower knowledge scores among undergraduate students highlight the need to refine the current dental curriculum, including infectious diseases epidemiology and control practices.…”
Section: Discussionsupporting
confidence: 88%
“…Continuous education and assessment in the clinical setting may aid in improving the learning outcomes [47]. During the COVID-19 pandemic, the lack of practical training among students emerged as a concern, which can be addressed through new technological innovations [46][47][48][49][50]. Educators need to be trained for adopting new virtual platforms of teaching, which could be used in the future crisis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,16,17 Our study is the first to examine the knowledge and perception on COVID-19 of dentistry students in Austria, and one of a few international surveys to focus on questioning dentistry students. [18][19][20] This study sought to provide an overview of the student's perceptions of the novel virus and attitudes to infection control shortly after the first implemented lockdown by the Austrian government. Dentistry students in their clinical courses are in direct contact with patients and therefore at a higher risk to get infected with COVID-19 due to work with rotative instruments and aerosol build up.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have mentioned that adherence to biosafety protocols by dental health professionals is high [ 6 ]. The relationship of other variables and conditions related to the pandemic cannot be ignored, among which could be mentioned the level of knowledge about COVID-19, preventive behaviors and practices as well as the availability of training courses for the management of this pandemic in dentist and dental students [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%